EXPLORING QUIZLET'S ROLE IN TECHNOLOGY-ENHANCED ENGLISH LANGUAGE LEARNING: A SYSTEMATIC REVIEW - Phalaguna, Ida Bagus; Budiarte, Agus; Subawa, I Wayan Putra Adi (Yavana Bhasha : Journal of English Language Education, 2026)
This systematic literature review critically evaluates the impact of Quizlet, a widely used digital flashcard tool, on English language learning outcomes, specifically focusing on vocabulary retention, learner engagement, and motivation. A comprehensive search across multiple electronic databases (Google Scholar, PubMed, SpringerLink, Elsevier) yielded 25 peer-reviewed studies published between 2010 and 2025, meeting predefined inclusion criteria. The findings indicate that Quizlet significantly enhances vocabulary retention, especially through spaced repetition and multiple retrieval practices, showing moderate to large effect sizes for both immediate and delayed vocabulary recall. Most studies reported positive outcomes in learner engagement, with participants demonstrating higher intrinsic motivation and increased study frequency compared to traditional learning methods. However, the review also identifies substantial heterogeneity in study designs, outcome measures, and learner contexts, limiting the ability to make robust causal inferences. The majority of studies employed non-randomized, quasi-experimental designs, reducing the strength of conclusions drawn from these findings. Furthermore, issues such as inconsistent reporting of participant demographics and sampling methods, as well as reliance on self-reported engagement and motivation, add to the variability of results. Despite these limitations, Quizlet’s potential in promoting autonomous learning, enhancing motivation, and improving language retention is evident. The review recommends future research to address methodological gaps, particularly through randomized controlled trials with diverse participant samples and standardized outcome measures, and suggests investigating Quizlet’s effectiveness in broader language domains beyond vocabulary acquisition.